Ceramic electronic component and method for manufacturing the same

By using dielectric grains with core-binoshell structures in the dielectric layer of ceramic electronic components to control the concentration ratio of rare earth elements, the reliability and insulation resistance degradation of ceramic electronic components in high capacitance and harsh environments is solved, and the high temperature life characteristics and capacitance temperature coefficient are improved.

CN113257571BActive Publication Date: 2025-04-04SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110134970.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-07
Filing Date
2021-01-29
Publication Date
2025-04-04
Estimated Expiration
2041-01-29

AI Technical Summary

Technical Problem

Existing ceramic electronic components have problems of reliability and deterioration in high capacitance and harsh use environments, especially under high temperature and high voltage conditions.

Method used

Using dielectric grains with core-bishell structures, the high temperature lifetime characteristics and capacitance temperature coefficient (TCC) characteristics of the dielectric layer are ensured by controlling the concentration ratio of different types of rare earth elements in the first and second shells.

Benefits of technology

Significantly improves the reliability and high temperature life characteristics of ceramic electronic components, ensuring stable performance in high capacitance and harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113257571B_ABST
    Figure CN113257571B_ABST
Patent Text Reader

Abstract

The present disclosure provides a ceramic electronic component and a method for manufacturing the ceramic electronic component, wherein the ceramic electronic component includes a body, wherein the body includes a dielectric layer and an internal electrode. The dielectric layer includes a plurality of dielectric grains, and at least one of the plurality of dielectric grains has a core-double shell structure, wherein the core-double shell structure has a core and a double shell. The double shell includes a first shell surrounding at least a portion of the core and a second shell surrounding at least a portion of the first shell. The double shell contains different types of rare earth elements R1 and R2, and R2 S1 / R1 S1 0.01 or less, R2 S2 / R1 S1 0.5 to 3.0, where R1 S1 represents the concentration of R1 contained in the first shell, and R2 S1 and R2 S2 represent the concentration of R2 contained in the first shell and the concentration of R2 contained in the second shell, respectively.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2020-0014955 filed on February 7, 2020, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety for all purposes by reference. Technical Field

[0002] The present disclosure relates to a ceramic electronic component and a method for manufacturing the ceramic electronic component. Background Art

[0003] Generally, ceramic electronic components using ceramic materials (such as capacitors, inductors, piezoelectric elements, varistors, thermistors, etc.) may include a ceramic body formed using ceramic materials, an internal electrode disposed in the ceramic body, and an external electrode disposed on a surface of the ceramic body to be connected to the internal electrode.

[0004] Multilayer ceramic capacitors (MLCCs), a type of ceramic electronic component, are being developed to have increased capacitance through ultrathinning of their layers.

[0005] A high capacitance multilayer ceramic capacitor (MLCC) may include barium titanate (BaTiO 3 ) and nickel as the base material for the inner electrode.

[0006] Such a body is usually sintered in a reducing atmosphere. In this case, the dielectric in the body should be resistant to reduction.

[0007] However, due to the inherent characteristics of the oxide, oxygen in the oxide may escape under a reducing atmosphere during a sintering operation to generate oxygen vacancies and electrons, and thus the reliability and insulation resistance (IR) of the oxide may be deteriorated.

[0008] In order to solve the above problems, a method of adding rare earth elements such as Dy, Y, and Ho to suppress the generation of oxygen vacancies, reduce the mobility of oxygen vacancies, and remove electrons generated by the added transition metals has been proposed.

[0009] However, there is still a problem that the above method may not be effective when the layers in the multilayer ceramic capacitor are thinned to have a relatively high capacitance, or when a relatively high voltage is used therein under a more severe use environment.

[0010] In addition, when a rare earth element or a transition element is added in the above method, high temperature life characteristics may be deteriorated, or temperature coefficient of capacitance (TCC) characteristics according to temperature change may be deteriorated. Summary of the invention

[0011] An aspect of the present disclosure is to provide a ceramic electronic component capable of improving reliability and a method of manufacturing the ceramic electronic component.

[0012] An aspect of the present disclosure is to provide a ceramic electronic component capable of improving high temperature life characteristics and a method of manufacturing the ceramic electronic component.

[0013] An aspect of the present disclosure is to provide a ceramic electronic component capable of improving a temperature coefficient of capacitance (TCC) characteristic and a method of manufacturing the ceramic electronic component.

[0014] However, the objects of the present disclosure are not limited to the above description and will be more easily understood in the course of describing specific embodiments of the present disclosure.

[0015] According to one aspect of the present disclosure, a ceramic electronic component includes: a body including a dielectric layer and an inner electrode; and an outer electrode disposed on the body and connected to the inner electrode. The dielectric layer includes a plurality of dielectric grains, and at least one of the plurality of dielectric grains has a core-double shell structure having a core and a double shell. The double shell includes a first shell surrounding at least a portion of the core and a second shell surrounding at least a portion of the first shell. The double shell contains different types of rare earth elements R1 and R2, and R2 S1 / R1 S1 is 0.01 or less, and R2 S2 / R1 S1 0.5 to 3.0, where R1 S1 represents the concentration of R1 contained in the first shell, and R2 S1 and R2 S2 represent the concentration of R2 contained in the first shell and the concentration of R2 contained in the second shell, respectively.

[0016] According to one aspect of the present disclosure, a method for manufacturing a ceramic electronic component includes: preparing a base material powder having a core-shell structure having a core and a shell, wherein the shell contains a rare earth element R1; adding a subcomponent containing a rare earth element R2 different from the rare earth element R1 to the base material powder to prepare a ceramic green sheet; printing a conductive paste for an internal electrode on the ceramic green sheet, and then laminating the printed ceramic green sheets to prepare a laminate; sintering the laminate to prepare a body including a dielectric layer and an internal electrode; and forming an external electrode on the body. The content of R2 is 0.1 to 3.0 times the content of R1. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and other aspects, features and advantages of the present disclosure will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which:

[0018] Figure 1 is a schematic perspective view showing a ceramic electronic component according to an embodiment of the present disclosure.

[0019] Figure 2 is along Figure 1 Schematic cross-sectional view taken along line II' in FIG.

[0020] Figure 3 is along Figure 1 Schematic cross-sectional view taken along line II-II'.

[0021] Figure 4 is a schematic exploded perspective view illustrating a body in which a dielectric layer and an internal electrode are stacked according to an embodiment of the present disclosure.

[0022] Figure 5 yes Figure 2 Magnified view of area P.

[0023] Figure 6 is a schematic diagram showing a grain having a core-double shell structure.

[0024] Figure 7 The intensity of Y measured as a result of X-ray fluorescence (XRF) energy dispersive endoscopy (EDS) line analysis of grains having a core-double shell structure of the inventive example of Test No. 2 is shown.

[0025] Figure 8 The intensity of Dy measured as a result of XRF EDS line analysis of the grains having a core-double shell structure of the inventive example of Test No. 2 is shown. DETAILED DESCRIPTION

[0026] Hereinafter, embodiments of the present disclosure will be described with reference to specific embodiments and the accompanying drawings. However, embodiments of the present disclosure may be modified to have various other forms, and the scope of the present disclosure is not limited to the embodiments described below. In addition, embodiments of the present disclosure may be provided to more completely describe the present disclosure to those of ordinary skill. Therefore, for clarity of description, the shapes and sizes of the elements in the accompanying drawings may be exaggerated, and the elements indicated by the same reference numerals in the accompanying drawings may be the same elements.

[0027] The values ​​of parameters used to describe, such as one-dimensional dimensions of an element (including but not limited to length, width, thickness, diameter, distance, gap and / or size), two-dimensional dimensions of an element (including but not limited to area and / or size), three-dimensional dimensions of an element (including but not limited to volume and / or size), and properties of an element (including but not limited to roughness, density, weight, weight ratio and / or molar ratio) can be obtained by the methods and / or tools described in the present disclosure. However, the present disclosure is not limited thereto. Even if not described in the present disclosure, other methods and / or tools understood by those of ordinary skill in the art may also be used.

[0028] In the accompanying drawings, for the clarity of the present disclosure, parts not related to the description will be omitted, and the thickness may be magnified to clearly show layers and regions. In addition, throughout the specification, unless otherwise specifically stated, when an element is referred to as "comprising" or "including" an element, it means that the element may also include other elements without departing from the present specification.

[0029] In the drawings, the X direction may be defined as the second direction, L direction or length direction; the Y direction may be defined as the third direction, W direction or width direction; and the Z direction may be defined as the first direction, stacking direction, T direction or thickness direction.

[0030] Ceramic electronic components

[0031] Figure 1 is a schematic perspective view showing a ceramic electronic component according to an embodiment of the present disclosure.

[0032] Figure 2 is along Figure 1 Schematic cross-sectional view taken along line II' in FIG.

[0033] Figure 3 is along Figure 1 Schematic cross-sectional view taken along line II-II'.

[0034] Figure 4 is a schematic exploded perspective view illustrating a body in which a dielectric layer and an internal electrode are stacked according to an embodiment of the present disclosure.

[0035] Figure 5 yes Figure 2 Magnified view of area P.

[0036] Figure 6 is a schematic diagram showing a grain having a core-double shell structure.

[0037] In the following, reference will be made to Figures 1 to 6The ceramic electronic component 100 according to an embodiment of the present disclosure is described in detail. In addition, a multilayer ceramic capacitor is described as an example of a ceramic electronic component, but the present disclosure is not limited thereto. In addition, ceramic electronic components using ceramic materials such as capacitors, inductors, piezoelectric elements, varistors, thermistors, etc. may also be applied.

[0038] The ceramic electronic component 100 according to the embodiment includes a body 110 and an external electrode 131 or 132. The body 110 includes a dielectric layer 111 and internal electrodes 121 and 122. The external electrodes 131 and 132 are disposed on the body 110 and connected to the internal electrodes 121 and 122, respectively. The dielectric layer 111 includes a plurality of dielectric grains 10a, 10b, and 10c. At least one of the plurality of dielectric grains 10a, 10b, and 10c has a core-double shell structure having a core C and a double shell. The double shell includes a first shell S1 surrounding at least a portion of the core C and a second shell S2 surrounding at least a portion of the first shell S1. The double shell includes different types of rare earth elements R1 and R2, and R2 S1 / R1 S1 is 0.01 or less, and R2 S2 / R1 S1 0.5 to 3.0, where R1 S1 and R1 S2 denote the concentration of R1 contained in the first shell and the concentration of R1 contained in the second shell, respectively, and R2 S1 and R2 S2 The concentrations of the rare earth elements R1 and R2 contained in the first shell and the second shell can be measured using XRF EDS line analysis. The intensities of the rare earth elements R1 and R2 detected using XRF EDS line analysis can be used to calculate R2 S1 / R1 S1 and R2 S2 / R1 S1 . R2 S1 / R1 S1 and R2 S2 / R1 S1 is the molar ratio.

[0039] In the body 110 , a plurality of dielectric layers 111 may be alternately stacked with internal electrodes 121 and 122 .

[0040] Although the specific shape of the body 110 is not necessarily limited, as shown in the figure, the body 110 may have a hexahedral shape, etc. Due to the shrinkage of the ceramic powder grains contained in the body 110 during the sintering process, the body 110 may not have a perfect hexahedral shape with completely straight lines, but may have a generally hexahedral shape as a whole.

[0041] The main body 110 may have a first surface 1 and a second surface 2 opposite to each other in the thickness direction (Z direction), a third surface 3 and a fourth surface 4 connected to the first surface 1 and the second surface 2 and opposite to each other in the length direction (X direction), and a fifth surface 5 and a sixth surface 6 connected to the first surface 1 and the second surface 2, connected to the third surface 3 and the fourth surface 4 and opposite to each other in the width direction (Y direction).

[0042] The plurality of dielectric layers 111 forming the body 110 may be in a sintered state, and adjacent dielectric layers 111 may be integrated with each other such that a boundary therebetween is not apparent without using a scanning electron microscope (SEM).

[0043] Reference Figure 5 Each dielectric layer 111 may include a plurality of dielectric grains, the plurality of dielectric grains including dielectric grains 10a, 10b, and 10c, and at least one of the plurality of dielectric grains may be a dielectric grain 10a having a core-double shell structure.

[0044] Reference Figure 6 , the dielectric grain 10 a having a core-double shell structure may include a first shell S1 surrounding at least a portion of the core C and a second shell S2 surrounding at least a portion of the first shell S1 .

[0045] The development of multilayer ceramic capacitors (MLCCs), which are an example of common ceramic electronic components, has focused on increasing the capacitance of the MLCCs and ultrathinning of the layers of the MLCCs.

[0046] With the increase in capacitance and the ultrathinning of layers, it is becoming increasingly difficult to ensure the withstand voltage characteristics of the dielectric layers in multilayer ceramic capacitors, and an increase in the defect rate caused by the degradation of the insulation resistance of the dielectric layers has become a problem.

[0047] In order to solve the above problems, a method of adding rare earth elements such as Dy, Y, Ho, etc. to suppress the generation of oxygen vacancies, reduce the mobility of oxygen vacancies, and remove electrons generated by the added transition metal has been proposed.

[0048] However, when the layers in the multilayer ceramic capacitor are thinned to have higher capacitance, or when a high voltage is used therein under a more severe use environment, there are still problems that cannot be solved by the above method.

[0049] Therefore, in the present disclosure, at least one of the plurality of dielectric grains has a core-double shell structure. In the core-double shell structure, the ratio of the concentration of the rare earth element contained in the first shell to the concentration of the rare earth element contained in the second shell can be controlled to ensure better high temperature life characteristics and temperature coefficient of capacitance (TCC) characteristics.

[0050] Therefore, in the present disclosure, at least one of the plurality of dielectric grains has a core-double shell structure. In the core-double shell structure, the double shell may contain different types of rare earth elements R1 and R2, and R2 may be hardly contained in the first shell. In addition, the ratio of the concentration of R1 contained in the first shell to the concentration of R2 contained in the second shell may be controlled to ensure high temperature life characteristics and TCC characteristics.

[0051] Rare earth elements can mainly replace perovskite structure (composed of ABO 3 The A site of the dielectric crystal grains is formed by reducing the oxygen vacancy concentration to form a shell region. The shell region can act as a barrier to prevent electrons from flowing at the grain boundaries of the dielectric grains, thereby preventing leakage current.

[0052] like Figure 5 and Figure 6 As shown, the first shell S1 may be provided to cover the entire surface of the core C, and the second shell S2 may be provided to cover the entire surface of the first shell S1. However, the first shell S1 may not cover a portion of the surface of the core C, and the second shell S2 may be directly deposited on the portion of the core C not covered by the first shell S1. In addition, the second shell S2 may not cover a portion of the surface of the first shell S1.

[0053] In this case, the first shell S1 may be provided to cover at least 90% of the area of ​​the surface of the core C, and the second shell S2 may be provided to cover at least 90% of the area of ​​the surface of the first shell S1. This is because when the first shell S1 is provided to cover an area less than 90% of the surface of the core and / or the second shell S2 is provided to cover an area less than 90% of the surface of the first shell S1, the effect of improving reliability according to the present disclosure may be insufficient.

[0054] The double shell contains different types of rare earth elements R1 and R2. The concentration of R1 contained in the first shell S1 can be defined as R1 S1 , the concentration of R1 contained in the second shell S2 can be defined as R1 S2 , the concentration of R2 contained in the first shell S1 can be defined as R2 S1 , and the concentration of R2 contained in the second shell S2 can be defined as R2 S2 .

[0055] The ratio of the concentration of R2 contained in the first shell S1 to the concentration of R1 contained in the first shell S1 (R2 S1 / R1 S1 ) is 0.01 or less (including 0). For example, R2 is substantially not contained in the first shell S1. When R2 S1 / R1 S1 When it is greater than 0.01, the effect of improving reliability according to the present disclosure may be insufficient.

[0056] In addition, the ratio of the concentration of R2 contained in the second shell S2 to the concentration of R1 contained in the first shell S1 (R2 S2 / R1 S1 ) satisfies 0.5 to 3.0.

[0057] When R2 S2 / R1 S1 When R2 is less than 0.5, the effect of improving reliability according to the present disclosure may be insufficient. S1 / R1 S1 When it is greater than 3.0, a secondary phase may be formed by the rare earth element, thereby deteriorating reliability.

[0058] When R2 S2 / R1 S1 When 0.5 to 3.0 is satisfied, the ratio of the concentration of R1 contained in the second shell S2 to the concentration of R1 contained in the first shell S1 (R1 S2 / R1 S1 ) can satisfy 0.1 to 1.3.

[0059] When R1 S2 / R1 S1 When it is less than 0.1, abnormal grain growth may be caused, and thus coarse grains may be formed, thereby deteriorating reliability. In addition, when R1 S2 / R1 S1 When it is greater than 1.3, a secondary phase may be formed by the rare earth element, thereby deteriorating reliability.

[0060] In the core C, the rare earth element may not be contained, or a relatively small amount of the rare earth element may be contained.

[0061] In addition, since the concentration of R1 or R2 varies significantly at the boundary between the core C and the first shell S1 and varies significantly at the boundary between the first shell S1 and the second shell S2, the core C, the first shell S1 and the second shell S2 can be easily distinguished and can be confirmed by transmission electron microscopy energy dispersive spectroscopy (TEM-EDS) analysis.

[0062] Reference Figure 6 , the distance LS2 corresponding to the thickness of the second shell S2 along the straight line connecting α and β can be 4% or more to 25% or less of the distance between α and β, wherein α represents the center of the core-double shell structure in the cross section of the core-double shell structure, and β represents the point on the outer surface of the second shell farthest from α. In this case, α may refer to the center of gravity of the dielectric grain in the cross section. The distance LS2 is measured using TEM-EDS. The distance LS2 may be measured by a method other than the TEM-EDS method that can be understood by those skilled in the art.

[0063] When the distance LS2 corresponding to the thickness of the second shell S2 along the straight line connecting α and β is less than 4%, the effect of improving reliability may be insufficient, and the effects of improving high temperature life characteristics and dielectric constant may be deteriorated.

[0064] Furthermore, when the distance LS2 corresponding to the thickness of the second shell along the straight line connecting α and β exceeds 25%, high temperature life characteristics may be deteriorated, or temperature coefficient of capacitance (TCC) characteristics changing according to temperature may be deteriorated.

[0065] In this case, a distance LS1 corresponding to the thickness of the first shell S1 along a straight line connecting α and β may be 5% or more to 30% or less of the distance between α and β.

[0066] When the distance LS1 corresponding to the thickness of the first shell S1 along the straight line connecting α and β is less than 5%, it may be difficult to achieve a double shell structure. When the distance LS1 corresponding to the thickness of the first shell S1 along the straight line connecting α and β exceeds 30%, it may be difficult to ensure reliability. The distance LS1 is measured using TEM-EDS. The distance LS1 may be measured by a method other than the TEM-EDS method that is understood by those skilled in the art.

[0067] In addition, when the thickness of the first shell S1 is greatly different from the thickness of the second shell S2, it may be difficult to improve both the high temperature life characteristics and the TCC characteristics. Therefore, the length LS1 corresponding to the thickness of the first shell in the straight line connecting α and β may be 0.5 to 1.5 times the length LS2 corresponding to the thickness of the second shell in the straight line connecting α and β.

[0068] Reference Figure 5 In addition to the dielectric grains 10a having the core-double shell structure, the dielectric layer 111 may further include dielectric grains 10b having the core-shell structure. Therefore, one or more of the plurality of dielectric grains may be dielectric grains 10b having the core-shell structure. The dielectric grains 10b having the core-shell structure may include a core 10b1 and a shell 10b2 surrounding at least a portion of the core 10b1.

[0069] In addition, the dielectric layer 111 may include dielectric grains 10 c without shells.

[0070] When the dielectric layer 111 includes dielectric grains 10c having no shell, the number of dielectric grains 10a having a core-double shell structure may be 50% or more relative to the total number of dielectric grains including the dielectric grains 10a, 10b, and 10c. The ratio of the number of dielectric grains having a core-double shell structure may be measured in an image of a cross section of the dielectric layer scanned by a transmission electron microscope (TEM).

[0071] When the number of dielectric grains having the core-double shell structure among the plurality of dielectric grains is less than 50%, the effect of improving high temperature life characteristics and TCC characteristics may be insufficient.

[0072] The dielectric layer 111 may include a dielectric layer having a 3 The material having the perovskite structure is represented as the main component.

[0073] For example, the dielectric layer 111 may include BaTiO 3 、(Ba,Ca)(Ti,Ca)O 3 、(Ba,Ca)(Ti,Zr)O 3 、Ba(Ti,Zr)O 3 and (Ba,Ca)(Ti,Sn)O 3 One or more of them are taken as the main components.

[0074] More specifically, for example, the dielectric layer 111 may include a material selected from BaTiO 3 、(Ba 1-x Ca x )(Ti 1-y Ca y ) 3 (where 0≤x≤0.3, 0≤y≤0.1), (Ba 1-x Ca x )(Ti 1-y Zr y ) 3 (where 0≤x≤0.3, 0≤y≤0.5), Ba(Ti 1-y Zr y ) 3 (where 0<y≤0.5) and (Ba 1-x Ca x )(Ti 1-y Sn y ) 3 One or more of the group consisting of (wherein 0≤x≤0.3, 0≤y≤0.1) is used as the main component.

[0075] The total content of R1 and R2 included in the dielectric layer 111 may be in the range of 0.1 mol to 15 mol relative to 100 mol of the main component.

[0076] When the sum of the contents of R1 and R2 contained in the dielectric layer 111 is less than 0.1 mol relative to 100 mol of the main component, it may be difficult to realize the core-double shell structure. When the sum of the contents of R1 and R2 contained in the dielectric layer 111 is greater than 15 mol relative to 100 mol of the main component, the sintering temperature may be significantly increased. Therefore, it may be difficult to obtain a dense microstructure.

[0077] The content of each of R1 and R2 contained in the dielectric layer 111 is not necessarily limited. However, in one embodiment of the present disclosure, the content of R1 contained in the dielectric layer 111 may be 0.1 mol to 4.0 mol relative to 100 mol of the main component, and the content of R2 contained in the dielectric layer 111 may be 0.01 mol to 12 mol relative to 100 mol of the main component. In more detail, the content of R1 contained in the dielectric layer 111 may be 0.1 mol to 2.5 mol relative to 100 mol of the main component, and the content of R2 contained in the dielectric layer 111 may be 0.01 mol to 7.5 mol relative to 100 mol of the main component.

[0078] In this case, R1 can be at least one selected from the group consisting of lanthanum (La), yttrium (Y), actinium (Ac), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and ruthenium (Ru), and R2 can be at least one element selected from the group that is not included in R1.

[0079] In addition, the present disclosure is not limited thereto. However, the ionic radius of the element selected from the group and included in R2 is larger than the ionic radius of the element selected from the group and included in R1. This is because when the ionic radius of the element included in R2 is larger than the ionic radius of the element included in R1, it is easier to achieve the effect of the core-double shell structure according to the present disclosure.

[0080] In addition, except that the rare earth element should be contained in the dielectric layer 111, the subcomponents contained in the dielectric layer 111 do not need to be limited, and appropriate elements and contents can be determined to obtain desired characteristics. For example, the dielectric layer may further include at least one of Mn, Cr, Ba, Si, Al, Mg, and Zr as a subcomponent.

[0081] The size of the dielectric grains need not be limited. For example, the average grain size of the dielectric grains in the dielectric layer 111 may be 50 nm or more to 500 nm or less. In addition to the Feret diameter method, the average grain size may also be measured by methods understood by those skilled in the art.

[0082] When the average grain size is less than 50 nm, the expected effect of deficiency in dissolution of an added element due to a decrease in dielectric constant and a decrease in grain growth rate may be insufficient. When the average grain size is greater than 500 nm, the change in capacitance according to temperature and DC voltage may increase due to a decrease in the number of dielectric grains per unit volume of the dielectric layer, and reliability may deteriorate.

[0083] The body 110 may include a capacitor forming portion A, which is arranged in the body 110 and includes a first internal electrode 121 and a second internal electrode 122, the first internal electrode 121 and the second internal electrode 122 are arranged to be opposite to each other and the corresponding dielectric layer 111 is interposed therebetween to form a capacitor, and an upper cover portion 112 and a lower cover portion 113 are respectively formed above and below the capacitor forming portion A.

[0084] In addition, the capacitance forming part A may be a portion that contributes to the capacitance formation of the capacitor and may be formed by alternately stacking a plurality of first internal electrodes 121 and a plurality of second internal electrodes 122 with respective dielectric layers 111 interposed therebetween.

[0085] The upper cover portion 112 and the lower cover portion 113 may be formed by stacking a single dielectric layer or two or more dielectric layers on the upper surface and the lower surface of the capacitor forming portion in the vertical direction, respectively, and may be mainly used to prevent physical or chemical damage to prevent the internal electrodes 121 and 122 from being damaged by external physical or chemical stress.

[0086] The upper cover portion 112 and the lower cover portion 113 may not include an internal electrode, and may include the same material as the dielectric layer 111 .

[0087] For example, the upper cover 112 and the lower cover 113 may include a ceramic material, for example, may include barium titanate (BaTiO 3 ) based ceramic materials.

[0088] In addition, the edge portion 114 and the edge portion 115 may be provided on the side surface of the capacitance forming portion A.

[0089] The edge portion 114 may be disposed on the sixth surface 6 of the body 110, and the edge portion 115 may be disposed on the fifth surface 5 of the body 110. For example, the edge portion 114 and the edge portion 115 may be disposed on both side surfaces of the body 110 opposite to each other in the width direction.

[0090] like Figure 3As shown, the edge portions 114 and 115 may refer to regions between ends of the first and second internal electrodes 121 and 122 and boundary surfaces of the body 110 in a cross section cut in a width-thickness (WT) direction of the body 110 .

[0091] The edge parts 114 and 115 may mainly serve to prevent the inner electrodes from being damaged due to external physical or chemical stress.

[0092] The edge portion 114 and the edge portion 115 may be formed by not applying the conductive paste to the ceramic green sheet at the region where the edge portion is to be formed.

[0093] In order to suppress steps formed by the internal electrodes 121 and 122, after the lamination operation, the internal electrodes may be cut to be exposed from the fifth surface 5 and the sixth surface 6 of the body 110. Then, a single dielectric layer or two or more dielectric layers may be laminated on the two exposed surfaces of the capacitance forming part A in the width direction to form edge portions 114 and 115.

[0094] The internal electrodes 121 and 122 may be alternately stacked with the dielectric layers 111 .

[0095] The internal electrodes 121 and 122 may include a first internal electrode 121 and a second internal electrode 122. The first internal electrodes 121 and the second internal electrodes 122 may be alternately arranged to be opposite to each other with the corresponding dielectric layer 111 constituting the body 110 interposed therebetween, and the first internal electrodes 121 and the second internal electrodes 122 may be exposed to the third surface 3 and the fourth surface 4 of the body 110, respectively.

[0096] Reference Figure 2 , the first internal electrode 121 may be spaced apart from the fourth surface 4 and may be exposed from the third surface 3 , and the second internal electrode 122 may be spaced apart from the third surface 3 and may be exposed from the fourth surface 4 .

[0097] In this case, the first and second internal electrodes 121 and 122 may be electrically separated from each other by the respective dielectric layers 111 interposed therebetween.

[0098] Reference Figure 3 , the body 110 may be formed by alternately stacking ceramic green sheets having the first internal electrodes 121 printed thereon and ceramic green sheets having the second internal electrodes 122 printed thereon, and then sintering the stacked ceramic green sheet laminate.

[0099] The material for forming the internal electrodes 121 and 122 is not necessarily limited, and a material having improved conductivity may be used. For example, the internal electrodes 121 and 122 may be formed by printing a conductive paste for internal electrodes on a ceramic green sheet, the conductive paste containing at least one of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.

[0100] As a printing method of the conductive paste for the internal electrode, a screen printing method, a gravure printing method, etc. may be used, but the present disclosure is not limited thereto.

[0101] In order to achieve miniaturization and high capacitance of multilayer ceramic capacitors, the thickness of the dielectric layer and the inner electrode should be thinned to increase the number of stacked layers. Therefore, generally, as the dielectric layer and the inner electrode become thinner, reliability may deteriorate, and characteristics such as insulation resistance, breakdown voltage, etc. may deteriorate.

[0102] However, in the embodiment of the present invention, as the dielectric layer and the internal electrode are thinned, the effect of improving reliability according to the present disclosure may be significantly improved.

[0103] In particular, when the thickness (te) of the internal electrodes 121 and 122 or the thickness (td) of the dielectric layer 111 is 0.41 μm or less, the effect of improving high temperature life characteristics and TCC characteristics according to the present disclosure may be significantly improved.

[0104] The thickness (te) of the internal electrodes 121 and 122 may refer to an average thickness of the first internal electrode 121 and the second internal electrode 122 .

[0105] The thickness (te) of the internal electrodes 121 and 122 may be measured by scanning an image of a cross section (LT cross section) of the body 110 in the third direction and the first direction using a scanning electron microscope (SEM).

[0106] For example, for five internal electrode layers including a reference internal electrode layer and two upper internal electrode layers and two lower internal electrode layers respectively arranged above and below the reference internal electrode layer, extracted from an image of a cross-section (LT cross-section) of the main body 110 in the third direction and the first direction cut at the central part of the main body 110 in the width direction by scanning a scanning electron microscope (SEM), based on the reference internal electrode layer, the point where the center line in the length direction of the main body and the center line in the thickness direction of the main body intersect, the thickness (te) of the internal electrodes 121 and 122 can be determined in the following manner: two points to the left and two points to the right from the reference center point at equal intervals in the reference internal electrode layer, the thickness of each defined point is measured, and an average value is obtained therefrom.

[0107] For example, for the above-mentioned five internal electrode layers, since the thickness at the reference center point at the point where the center line of the reference internal electrode layer in the length direction of the body and the center line in the thickness direction of the body intersect and the thickness at each of two points to the left and right at equal intervals from the reference center point (every 500nm) can be measured, the thickness (te) of the internal electrode 121 and the internal electrode 122 can be determined as the average value of the thicknesses of a total of 25 points.

[0108] The thickness (td) of the dielectric layer 111 may refer to an average thickness of the dielectric layer 111 disposed between the first and second internal electrodes 121 and 122 .

[0109] Similar to the thickness (te) of the internal electrode, the thickness (td) of the dielectric layer 111 may be measured by scanning an image of a cross section (LT cross section) of the body 110 in the third direction and the first direction using a scanning electron microscope (SEM).

[0110] For example, for five dielectric layers including a reference dielectric layer and two upper dielectric layers and two lower dielectric layers respectively arranged above and below the reference dielectric layer, extracted from an image of a cross-section (LT cross-section) of the main body 110 in the third direction and the first direction cut at the central part of the main body 110 in the width direction by scanning a scanning electron microscope (SEM), based on the reference dielectric layer, the point where the center line in the length direction of the main body and the center line in the thickness direction of the main body intersect, the thickness (td) of the dielectric layer 111 can be determined as follows: two points to the left and two points to the right from the reference center point at equal intervals in the reference dielectric layer, the thickness of each defined point is measured, and an average value is obtained therefrom.

[0111] For example, for the above-mentioned five dielectric layers, since the thickness at the reference center point where the center line in the length direction of the body and the center line in the thickness direction of the body intersect in the reference dielectric layer and the thickness at each of two points to the left and right at equal intervals from the reference center point (every 500 nm) can be measured, the thickness (td) of the dielectric layer 111 can be determined as the average value of the thicknesses of a total of 25 points.

[0112] The external electrodes 131 and 132 may be disposed on the body 110 and may be connected to the internal electrodes 121 and 122 , respectively.

[0113] like Figure 2 As shown, the first and second external electrodes 131 and 132 may be disposed on the third and fourth surfaces 3 and 4 of the body 110 , respectively, and may be connected to the first and second internal electrodes 121 and 122 , respectively.

[0114] In the present embodiment, a structure in which the ceramic electronic component 100 has two external electrodes 131 and 132 is described, but the number, shape, etc. of the external electrodes 131 and 132 may be changed according to the shape of the internal electrodes 121 and 122 or other purposes.

[0115] The external electrodes 131 and 132 may be formed using any material such as metal as long as it may have conductivity, a specific material may be determined in consideration of electrical characteristics, structural stability, etc., and may have a multi-layered structure.

[0116] For example, the external electrodes 131 and 132 may include electrode layers 131 a and 132 a and plating layers 131 b and 132 b formed on the electrode layers 131 a and 132 a , respectively.

[0117] As more specific examples of the electrode layers 131 a and 132 a , the electrode layers 131 a and 132 a may be sintered electrodes including a conductive metal and glass, or resin-based electrodes including a conductive metal and resin.

[0118] In addition, the electrode layers 131a and 132a may have a form in which a sintered electrode and a resin-based electrode are sequentially formed on the body 110. In addition, the electrode layers 131a and 132a may be formed by transferring a sheet containing a conductive metal onto the body 110, or may be formed by transferring a sheet containing a conductive metal onto a sintered electrode.

[0119] The conductive metal used for the electrode layers 131a and 132a is not particularly limited as long as it is a material that can be electrically connected to the internal electrodes to form a capacitor. For example, the conductive metal may be one or more of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.

[0120] The plating layers 131 b and 132 b may be plating layers including at least one of nickel (Ni), tin (Sn), palladium (Pd), and alloys thereof, and may include a plurality of layers.

[0121] As a more specific example of the plating layers 131b and 132b, the plating layers 131b and 132b may be nickel (Ni) plating layers or tin (Sn) plating layers, may have a form in which a nickel (Ni) plating layer and a tin (Sn) plating layer are sequentially formed on the electrode layers 131a and 132a, or may have a form in which a tin (Sn) plating layer, a nickel (Ni) plating layer, and another tin (Sn) plating layer are sequentially formed. In addition, the plating layers 131b and 132b may include a plurality of nickel (Ni) plating layers and / or a plurality of tin (Sn) plating layers.

[0122] Method for manufacturing ceramic electronic components

[0123] Hereinafter, a method of manufacturing a ceramic electronic component according to another aspect of the present disclosure will be described in detail. However, descriptions overlapping with those in the ceramic electronic component will be omitted to avoid duplication of descriptions.

[0124] According to another aspect of the present disclosure, a method for manufacturing a ceramic electronic component includes: preparing a base material powder having a core-shell structure having a core and a shell, the shell containing a rare earth element R1; adding a subcomponent containing another type of rare earth element R2 different from the rare earth element R1 to the base material powder to prepare a ceramic green sheet; printing a conductive paste for an internal electrode on the ceramic green sheet, and then laminating the printed ceramic green sheets to prepare a laminate; sintering the laminate to prepare a body including a dielectric layer and an internal electrode; and forming an external electrode on the body. The content of R2 in the base material powder is 0.1 to 3.0 times the content of R1.

[0125] A base material powder having a core-shell structure having a core and a shell, the shell containing a rare earth element, may be prepared.

[0126] When the base material powder does not have a core-shell structure, it may be difficult to realize dielectric grains having a core-double shell structure according to the present disclosure.

[0127] The method for manufacturing the base material powder having a core-shell structure is not necessarily limited. For example, when BaTiO is prepared by a hydrothermal synthesis process 3 When the base material powder is prepared, rare earth elements may be added during the process of growing the powder to a desired size to synthesize the base material powder. 3 After mixing with rare earth elements, a base material powder having a core-shell structure can be prepared by heat treatment.

[0128] Next, a secondary component including a rare earth element R2 different from the rare earth element R1 may be added to the base material powder to prepare a ceramic green sheet. In this case, after the secondary component is added to the base material powder, ethanol and toluene as a solvent may be mixed with a dispersant, and may be further mixed with a binder to prepare a ceramic green sheet.

[0129] In order to realize the dielectric grains having the core-double shell structure according to the present disclosure, the content of the rare earth element R2 as a subcomponent contained in the base material powder may be controlled to be 0.1 to 3.0 times the content of the rare earth element R1 contained in the base material powder.

[0130] When the content of R2 contained in the base material powder is less than 0.1 times the content of R1, it may be difficult to realize the dielectric grains having a core-double shell structure according to the present disclosure. When the content of R2 contained in the base material powder is greater than 3.0 times the content of R1, a secondary phase may be formed by the rare earth element to deteriorate reliability.

[0131] The elements contained in the subcomponents other than the rare earth element are not necessarily limited and may be appropriately controlled to obtain desired characteristics.

[0132] Next, after printing a conductive paste for an internal electrode on the ceramic green sheet, a plurality of printed ceramic green sheets may be stacked to prepare a stacked body.

[0133] Next, the stacked body may be sintered to prepare a body including a dielectric layer and internal electrodes.

[0134] The dielectric layer 111 includes a plurality of dielectric grains 10a, 10b, and 10c. At least one of the plurality of dielectric grains 10a, 10b, and 10c has a core-double shell structure having a core C and a double shell. The double shell includes a first shell S1 surrounding at least a portion of the core C and a second shell S2 surrounding at least a portion of the first shell S1. The double shell includes at least two different types of rare earth elements R1 and R2, and R2 S1 / R1 S1 is 0.01 or less, and R2 S2 / R1 S1 0.5 to 3.0, where R1 S1 and R1 S2 denote the concentration of R1 contained in the first shell and the concentration of R1 contained in the second shell, respectively, and R2 S1 and R2 S2 represent the concentration of R2 contained in the first shell and the concentration of R2 contained in the second shell, respectively.

[0135] In order to satisfy R2 S1 / R1 S1 is 0.01 or less, and R2 S2 / R1 S1 In order to achieve the above relationship of 0.5 to 3.0, it is necessary to appropriately adjust the sintering temperature and the content of the rare earth element as a subcomponent added to the base material powder.

[0136] The specific numerical range of the sintering temperature may vary according to the type and amount of the added elements, but is not necessarily limited. For example, the sintering temperature may range from greater than 1230°C to less than 1280°C.

[0137] Next, external electrodes may be formed on the body to obtain a ceramic electronic component.

[0138] Example

[0139] The base material powders listed in Table 1 below were prepared. In this case, “1.5Y-doped BT” refers to a base material powder having a core-shell structure, in which 1.5Y-doped BT has a core-shell structure with respect to 100 mol of BaTiO 3 , containing 1.5 mol of Y in the shell. In addition, "0.5Ho-doped BT" refers to a base material powder having a core-shell structure, in which 100 mol of BaTiO 3 , containing 0.5 mol of Ho in the shell. In addition, “undoped BT” refers to BaTiO that does not have a core-shell structure. 3 powder.

[0140] Then, the accessory ingredients listed in Table 1 below are added to the base material powder and mixed with a dispersant using ethanol and toluene as solvents. Then, further mixed with a binder to prepare a ceramic green sheet. A nickel (Ni) electrode is printed on the prepared ceramic green sheet, and a plurality of printed ceramic green sheets are stacked, pressed and cut to prepare a plurality of sheets. A plurality of sheets are burned to remove the binder, and then a sintering operation is performed in a reducing atmosphere at a sintering temperature listed in Table 1 to prepare a sample sheet.

[0141] The dielectric constant, 125° C. TCC value, and high temperature life characteristics of the prepared sample pieces were measured and are listed in Table 2 below.

[0142] In each of the listed samples, the structure of the dielectric grains was analyzed by TEM-EDS analysis and is listed in Table 2.

[0143] The 125°C TCC value was measured using an LCR meter in the temperature range of -55°C to 125°C at 1 kHz and 1 V.

[0144] The high temperature life characteristics test (high temperature IR boost test) was conducted on 40 samples of each test number in the following manner: the conditions including 150°C and 1Vr=10V / μm were maintained for 30 minutes, the voltage was increased, and the average value of the failure voltage value was calculated, and the calculated average value was listed. In this case, "1Vr" refers to 1 reference voltage, and "10V / μm" refers to a voltage of 10 volts per 1μm (dielectric thickness).

[0145] In addition, the cross-sections (LT cross-sections) of the sample pieces in the length direction and the thickness direction (cut in the central part of each sample piece in the width direction) were analyzed by transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS) equipment to list concentration 1*, concentration 2*, length* and fraction* in Table 2. TEM was 200 kV ARM, and confirmation was performed with spot 4, 100000 times. STEM-EDS measured 100 points at intervals of 10 nm.

[0146] Concentration 1* and concentration 2* are determined by performing line analysis of energy dispersive X-ray spectroscopy (EDS) mounted on a transmission electron microscope (TEM) on grains each having a core-double shell structure to obtain an intensity value for each of Y and Dy. S2 Divide by the value R1 S1 To obtain the concentration 1*, the value R1 S2 is the value obtained by subtracting the intensity of Y in the core region from the intensity of Y in the second shell, and the value R1 S1 is the value obtained by subtracting the Y intensity in the core region from the Y intensity in the first shell. S2 Divide by the value R1 S1 To obtain the concentration 2*, the value R2 S2 is the value obtained by subtracting the intensity of Dy in the core region from the intensity of Dy in the second shell, and the value R1 S1 is the value obtained by subtracting the intensity of Y in the core region from the intensity of Y in the first shell.

[0147] like Figure 7 and Figure 8 As shown, the length* was obtained by performing TEM EDS line analysis on grains each having a core-double shell structure, and the result of [the number of points measured in LS2] / [the total number of points measured from α to β] is listed.

[0148] The score* is obtained by measuring the ratio of the number of grains each having a core-double shell structure to the total number of dielectric grains in a 10 μm×10 μm area of ​​the central portion (LT cross section) of the cross section in the length direction and the thickness direction.

[0149] Table 1

[0150]

[0151] Table 2

[0152]

[0153] (DC: dielectric constant, C1: concentration 1, C2: concentration 2, L: length, F: fraction, CE: comparative example, IE: inventive example)

[0154] As can be seen from Tables 1 and 2, test numbers 2, 3, 4, 8, and 9, whose concentration 2* satisfies 0.5 to 3.0, have improved high temperature life reliability. In addition, test numbers 2, 3, 4, 8, and 9 have improved dielectric constants and improved 125°C TCC characteristics.

[0155] Furthermore, test numbers 11 and 12 (excluding grains having a core-double shell structure) have poor high temperature life reliability.

[0156] In addition, test numbers 1, 5 and 6 have a core-double shell structure, but the concentration 2*(R2 S2 / R1 S1 ) does not satisfy the value of 0.5 to 3.0, so the high temperature life reliability is poor.

[0157] In the case of test number 7, the concentration 2*(R2 S2 / R1 S1 ) satisfies a value of 0.5 to 3.0, but the second shell has a rather short length, or the fraction of grains having a core-double shell structure is low, and therefore, high temperature life reliability is poor.

[0158] In the case of test number 10, the concentration 2*(R2 S2 / R1 S1 ) value satisfies 0.5 to 3.0, but the concentration 1*(R1 S2 / R1 S1 ) value is low, so the high temperature life reliability is poor.

[0159] Figure 7 The intensity of Y measured as a result of XRF EDS line analysis of the grains having a core-double shell structure as the inventive example of Test No. 2 is shown.

[0160] exist Figure 7 , the intensity of Y in the core portion is about 18 on average, which indicates that Y does not exist in the core portion. In addition, the intensity of Y and the length LC corresponding to the radius of the core portion may vary depending on the TEM equipment, measurement conditions, and environment, but the portion with the lowest value in the measured intensity may be regarded as the core region and may be regarded as the portion in which Y does not exist.

[0161] The intensity of Y in the first shell S1 is about 48 on average, and the intensity of Y in the second shell S2 is about 33 on average. Therefore, R1 S2 / R1 S1 It can be obtained by dividing the value obtained by subtracting 18 from the intensity of Y in the second shell by the value obtained by subtracting 18 from the intensity of Y in the first shell. For example, R1S2 / R1 S1 =(33-18) / (48-18)=0.5.

[0162] Figure 8 The intensity of Dy measured as a result of XRF EDS line analysis of the grains having a core-double shell structure as the inventive example of Test No. 2 is shown.

[0163] exist Figure 8 , the intensity of Dy in the core and the first shell is about 18 on average, which indicates that Dy does not exist in the core and the first shell. In addition, the intensity of Dy corresponding to the length LC of the radius of the core may vary depending on the TEM equipment, measurement conditions, and environment, but the portion with the lowest value in the measured intensity may be regarded as the core region and may be regarded as a portion in which Dy does not exist.

[0164] The intensity of Dy in the second shell S2 is about 54 on average. Therefore, R2 can be obtained by dividing the value obtained by subtracting 18 from the intensity of Dy in the second shell by the value obtained by subtracting 18 from the intensity of Y in the first shell. S2 / R1 S1 For example, R2 S2 / R1 S1 =(54-18) / (48-18)=1.20.

[0165] As described above, among the plurality of dielectric grains, at least one grain may have a core-double shell structure. Therefore, the reliability of the ceramic electronic component may be improved.

[0166] In the core-double shell structure, the concentration of the rare earth element contained in the first shell and the concentration of the rare earth element contained in the second shell may be controlled to improve high temperature life characteristics and TCC characteristics.

[0167] While embodiments have been shown and described above, it will be apparent to those skilled in the art that modifications and variations may be made without departing from the scope of the present disclosure as defined by the appended claims.

Claims

1. A ceramic electronic component, comprising: a body including a dielectric layer and an inner electrode; and an outer electrode disposed on the body and connected to the inner electrode, Wherein, the dielectric layer includes a plurality of dielectric grains. in, At least one of the plurality of dielectric grains has a core-double shell structure having a core and double shells, The double shell includes a first shell surrounding at least a portion of the core and a second shell surrounding at least a portion of the first shell, The double shell contains different types of rare earth elements R1 and R2, and R2 S1 / R1 S1 0.01 or less, R2 S2 / R1 S1 is 0.5 to 3.0, and R1 S2 / R1 S1 is 0.1 to 1.3, where R1 S1 and R1 S2 denote the concentration of R1 contained in the first shell and the second shell, respectively, and R2 S1 and R2 S2 represent the concentration of R2 contained in the first shell and the concentration of R2 contained in the second shell, respectively, R2 S1 / R1 S1 , R2 S2 / R1 S1 and R1 S2 / R1 S1 Indicates the molar ratio.

2. The ceramic electronic component according to claim 1, wherein: A distance corresponding to the thickness of the second shell along a straight line connecting α and β is 4% or more to 25% or less of the distance between α and β, wherein α represents the center of the core-double shell structure in a cross section of the core-double shell structure, and β represents the point on the outer surface of the second shell farthest from α.

3. The ceramic electronic component according to claim 2, wherein: A distance along the straight line connecting α and β corresponding to the thickness of the first shell is 5% or more and 30% or less of the distance between α and β.

4. The ceramic electronic component according to claim 2, wherein: The distance along the straight line connecting α and β corresponding to the thickness of the first shell is 0.5 to 1.5 times the distance along the straight line connecting α and β corresponding to the thickness of the second shell.

5. The ceramic electronic component according to claim 1, wherein: The first shell of the core-double shell structure is configured to cover 90% or more of the surface area of ​​the core, and The second shell of the core-double shell structure is configured to cover 90% or more of the surface area of ​​the first shell.

6. The ceramic electronic component according to claim 1, wherein: At least one dielectric grain among the plurality of dielectric grains has a core-shell structure having a core and a shell.

7. The ceramic electronic component according to claim 1, wherein: The number of dielectric grains having the core-double shell structure is 50% or more of the number of the plurality of dielectric grains.

8. The ceramic electronic component according to claim 1, wherein: The dielectric layer includes one or more of BaTiO3, (Ba,Ca)(Ti,Ca)O3, (Ba,Ca)(Ti,Zr)O3, Ba(Ti,Zr)O3 and (Ba,Ca)(Ti,Sn)O3 as a main component.

9. The ceramic electronic component according to claim 8, wherein: The total content of R1 and R2 contained in the dielectric layer is 0.1 mol to 15 mol relative to 100 mol of the main component.

10. The ceramic electronic component according to claim 1, wherein: R1 comprises at least one selected from the group consisting of lanthanum, yttrium, actinium, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and ruthenium, and R2 contains at least one element selected from the group except the elements contained in R1.

11. The ceramic electronic component according to claim 1, wherein: The ionic radius of R2 is larger than that of R1.

12. The ceramic electronic component according to claim 8, wherein: The dielectric layer further includes at least one of Mn, Cr, Ba, Si, Al, Mg, and Zr as a subcomponent.

13. The ceramic electronic component according to claim 8, wherein: The dielectric layer includes one or more selected from the group consisting of: BaTiO3; (Ba 1-x Ca x )(Ti 1-y Ca y )O3, where 0≤x≤0.3, 0≤y≤0.1; (Ba 1-x Ca x )(Ti 1-y Zr y )O3, where 0≤x≤0.3, 0≤y≤0.5; Ba(Ti 1-y Zr y )O3, where 0<y≤0.5; and (Ba 1-x Ca x )(Ti 1-y Sn y )O3, where 0≤x≤0.3, 0≤y≤0.

1.

14. The ceramic electronic component according to claim 1, wherein: The thickness of the inner electrode is 0.41 μm or less, and / or the thickness of the dielectric layer is 0.41 μm or less.

15. A method for manufacturing a ceramic electronic component, the method comprising: Preparing a base material powder having a core-shell structure, wherein the core-shell structure has a core and a shell, wherein the shell contains a rare earth element R1; adding a subcomponent including a rare earth element R2 different from the rare earth element R1 to the base material powder to prepare a ceramic green sheet; printing a conductive paste for an internal electrode on the ceramic green sheets, and then laminating the printed ceramic green sheets to prepare a laminate; sintering the laminate to prepare a body including a dielectric layer and an internal electrode; and forming an external electrode on the body, The content of R2 is 0.1 to 3.0 times that of R1. Wherein, the dielectric layer includes a plurality of dielectric grains. At least one of the plurality of dielectric grains has a core-double shell structure having a core and double shells, The double shell includes a first shell surrounding at least a portion of the core and a second shell surrounding at least a portion of the first shell, The double shell includes different types of rare earth elements R1 and R2, and R2 S2 / R1 S1 is 0.5 to 3.0, and R1 S2 / R1 S1 is 0.1 to 1.3, where R1 S1 and R1 S2 denote the concentration of R1 contained in the first shell and the second shell, respectively, and R2 S2 represents the concentration of R2 contained in the second shell, R2 S2 / R1 S1 and R1 S2 / R1 S1 Indicates the molar ratio.

16. The method according to claim 15, wherein: R2 S1 / R1 S1 is 0.01 or less, where R2 S1 represents the concentration of R2 contained in the first shell.

17. The method according to claim 16, wherein: The step of sintering the stacked body is performed by adjusting the sintering temperature so that R2 S1 / R1 S1 is 0.01 or less, and R2 S2 / R1 S1 0.5 to 3.

0.

18. The method according to claim 17, wherein: The sintering temperature is greater than 1230°C and less than 1280°C.

19. The method according to claim 15, wherein: R2 S2 / R1 S1 is 1.0 to 3.0, and R1 S2 / R1 S1 0.5 to 1.

3.

20. A ceramic electronic component comprising: a body including a dielectric layer and an inner electrode; and an outer electrode disposed on the body and connected to the inner electrode, Wherein, the dielectric layer includes a plurality of dielectric grains. in, At least one of the plurality of dielectric grains has a core-double shell structure having a core and double shells, The double shell includes a first shell surrounding at least a portion of the core and a second shell surrounding at least a portion of the first shell, The double shell contains different types of rare earth elements R1 and R2, R2 S1 / R1 S1 is 0.01 or less, and R2 S2 / R1 S1 0.5 to 3.0, where R1 S1 represents the concentration of R1 contained in the first shell, and R2 S1 and R2 S2 represent the concentration of R2 contained in the first shell and the concentration of R2 contained in the second shell, respectively, R2 S1 / R1 S1 and R2 S2 / R1 S1 represents the molar ratio, and A distance corresponding to the thickness of the second shell along a straight line connecting α and β is 4% or more to 25% or less of the distance between α and β, wherein α represents the center of the core-double shell structure in a cross section of the core-double shell structure, and β represents the point on the outer surface of the second shell farthest from α.

21. The ceramic electronic component according to claim 20, wherein: A distance along the straight line connecting α and β corresponding to the thickness of the first shell is 5% or more and 30% or less of the distance between α and β.

22. The ceramic electronic component according to claim 20, wherein: The distance along the straight line connecting α and β corresponding to the thickness of the first shell is 0.5 to 1.5 times the distance along the straight line connecting α and β corresponding to the thickness of the second shell.

23. The ceramic electronic component according to claim 20, wherein: The first shell of the core-double shell structure is configured to cover 90% or more of the surface area of ​​the core, and The second shell of the core-double shell structure is configured to cover 90% or more of the surface area of ​​the first shell.

24. The ceramic electronic component according to claim 20, wherein: At least one dielectric grain among the plurality of dielectric grains has a core-shell structure having a core and a shell.

25. The ceramic electronic component according to claim 20, wherein: The number of dielectric grains having the core-double shell structure is 50% or more of the number of the plurality of dielectric grains.

26. The ceramic electronic component according to claim 20, wherein: The dielectric layer includes one or more of BaTiO3, (Ba,Ca)(Ti,Ca)O3, (Ba,Ca)(Ti,Zr)O3, Ba(Ti,Zr)O3 and (Ba,Ca)(Ti,Sn)O3 as a main component.

27. The ceramic electronic component according to claim 26, wherein: The total content of R1 and R2 contained in the dielectric layer is 0.1 mol to 15 mol relative to 100 mol of the main component.

28. The ceramic electronic component according to claim 20, wherein: R1 comprises at least one selected from the group consisting of lanthanum, yttrium, actinium, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and ruthenium, and R2 contains at least one element selected from the group except the elements contained in R1.

29. The ceramic electronic component according to claim 20, wherein: The ionic radius of R2 is larger than that of R1.

30. The ceramic electronic component according to claim 26, wherein: The dielectric layer further includes at least one of Mn, Cr, Ba, Si, Al, Mg, and Zr as a subcomponent.

31. The ceramic electronic component according to claim 26, wherein: The dielectric layer includes one or more selected from the group consisting of: BaTiO3; (Ba 1-x Ca x )(Ti 1-y Ca y )O3, where 0≤x≤0.3, 0≤y≤0.1; (Ba 1-x Ca x )(Ti 1-y Zr y )O3, where 0≤x≤0.3, 0≤y≤0.5; Ba(Ti 1-y Zr y )O3, where 0<y≤0.5; and (Ba 1-x Ca x )(Ti 1-y Sn y )O3, where 0≤x≤0.3, 0≤y≤0.

1.

32. The ceramic electronic component according to claim 20, wherein: The thickness of the inner electrode is 0.41 μm or less, and / or the thickness of the dielectric layer is 0.41 μm or less.

Citation Information

Patent Citations

  • Display device

    KR1020200014955A

  • Dielectric composition and multilayer ceramic capacitor containing same

    CN108063051A

  • Dielectric ceramic composition and electronic component

    JP2013129560A